Resveratrol alleviates lipopolysaccharide-induced liver injury by inducing SIRT1/P62-mediated mitophagy in gibel carp (Carassius gibelio) - Wu, Liyun; Chen, Qiaozhen; Dong, Bo; Geng, Hancheng; Wang, Yu; Han, Dong; Zhu, Xiaoming; Liu, Haokun; Zhang, Zhimin; Yang, Yunxia; Xie, Shouqi; Jin, Junyan (Frontiers in Immunology, 2023)
Resveratrol (RES) is a polyphenol organic compound with antioxidant and anti-inflammatory properties. This study aimed to determine whether and how RES can alleviate liver injury in lipopolysaccharide(LPS)-induced gibel carp. Thus, gibel carp were fed a diet with or without RES and were cultured for 8 weeks, followed by LPS injection. The results suggested that RES attenuated the resulting oxidative stress and inflammation by activating the Nrf2/Keap1 pathway and inhibiting the NF-κB pathway, as confirmed by changes in oxidative stress, inflammation-related gene expression, and antioxidant enzyme activity. Furthermore, RES cleared damaged mitochondria and enhanced mitochondrial biogenesis to mitigate ROS accumulation by upregulating the SIRT1/PGC-1α and PINK1/Parkin pathways and reducing p62 expression. Overall, RES alleviated LPS-induced oxidative stress and inflammation in gibel carp through mitochondria-related mechanisms.